Feasibility of a custom-tailored, evidence-based, theory-informed, intervention to prevent burnout and reduce stress for healthcare professionals: protocol for a single-arm trial - Marleen Schröter; Julia Berschick; Anna K. Koch; Julia K. Schiele; Martin Bogdanski; Melanie Steinmetz; Wiebke Stritter; Christian S. Kessler; Georg Seifert (Pilot and Feasibility Studies)
Abstract Background Healthcare professionals face high levels of occupational stress, time pressure, workload, and poor organizational support. This makes them particularly vulnerable to burnout. The COVID-19 pandemic has further exacerbated this situation. This single-arm, multicenter, mixed-methods feasibility study pilots the LAGOM program: A tailored, evidence-based intervention to prevent burnout and reduce stress among healthcare professionals. Methods Participants will include healthcare professionals (N = 30) working at Charité–Universitätsmedizin Berlin and Immanuel Hospital, Berlin. LAGOM focuses on support for individual behavior change and personal resources and also addresses the organizational level. The intervention´s feasibility will be evaluated through a non-randomized feasibility trial with a mixed methods process evaluation. The exploratory primary study aims are to assess the acceptability and feasibility of the (1) evaluation procedures and of the (2) intervention content and structure using study records, standardized questionnaires, protocol checklists, and diaries. Exploratory effectiveness analysis will take place as well. Further, semi-structured interviews (n = 3 to 6) and electrophysiological measurements (n = 20) will be conducted. Discussion Custom-tailored, well-implemented multi-level interventions are needed to prevent burnout and reduce stress among healthcare professionals. Long-term strategies are warranted to sustainably implement effective programs. This feasibility study helps to refine trial procedures and content of the LAGOM program for a randomized controlled trial to evaluate the intervention’s effectiveness. Trial registration German Clinical Trials Register: DRKS00032014 , registered 17th October 2023.